THE ROLE AND POTENTIAL OF ISLAM CAPITAL MARKET IN SUSTAINABLE ECONOMIC DEVELOPMENT - Dea Nabila, Dea; Selly Yulaikha; Maula Aji Hidayatullah; Elma Susanti; Megawati Oktaria; Meko Susanto; Tri Suci Aryanti (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2023)
Islam capital markets play an important role in promoting sustainable economic development through financial instruments that comply with Islam principles. The journal discusses the role of the Islam capital market as a source of funding and financial access in the context of sustainable economic development. Through the research method of literature studies that gather data through the study of libraries related to the discussion of this journal. In the results of the research found the important roles of capital markets in sustainable economic development, which to maximize the potential of the islam capital market in the sustainable development of the economy, cooperation between the government, financial institutions, and islam market players is necessary. However, in addition to the continued economic development, there are also obstacles within it. Where governments need to create regulations that support the development of Islam capital markets and integrate them into sustainable economic development strategies. Financial institutions and Islam capital market players need to continue to develop innovative products and services that meet market needs and promote sustainable business practices.